2017
DOI: 10.1021/jacs.7b06973
|View full text |Cite
|
Sign up to set email alerts
|

Self-Templated Formation of Interlaced Carbon Nanotubes Threaded Hollow Co3S4 Nanoboxes for High-Rate and Heat-Resistant Lithium–Sulfur Batteries

Abstract: Lithium-sulfur batteries (Li-S) have attracted soaring attention due to the particularly high energy density for advanced energy storage system. However, the practical application of Li-S batteries still faces multiple challenges, including the shuttle effect of intermediate polysulfides, the low conductivity of sulfur and the large volume variation of sulfur cathode. To overcome these issues, here we reported a self-templated approach to prepare interconnected carbon nanotubes inserted/wired hollow CoS nanobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
252
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(258 citation statements)
references
References 61 publications
6
252
0
Order By: Relevance
“…When cycled at 0.2 C, an initial capacity of 1015 mAh g −1 is attained for the 5.0 mg cm −2 electrode, corresponding to an areal capacity of 5.1 mAh cm −2 . The areal specific capacities under high sulfur loadings in this work are remarkable among the reported hybrid sulfur hosts (Figure 6d; Figure S17, Supporting Information), [17,20,25,[43][44][45][46][47] especially for the cycling at a high current density (1 C), where there has been a limited number of studies (Figure 6d). Further, the cycling stabilities of our hybrid electrodes could be well maintained even at high current densities.…”
Section: Doi: 101002/aenm201800201mentioning
confidence: 57%
“…When cycled at 0.2 C, an initial capacity of 1015 mAh g −1 is attained for the 5.0 mg cm −2 electrode, corresponding to an areal capacity of 5.1 mAh cm −2 . The areal specific capacities under high sulfur loadings in this work are remarkable among the reported hybrid sulfur hosts (Figure 6d; Figure S17, Supporting Information), [17,20,25,[43][44][45][46][47] especially for the cycling at a high current density (1 C), where there has been a limited number of studies (Figure 6d). Further, the cycling stabilities of our hybrid electrodes could be well maintained even at high current densities.…”
Section: Doi: 101002/aenm201800201mentioning
confidence: 57%
“…Simultaneously, the ample void volume can host S and accommodate the volume expansion. Liu and co‐workers prepared interlaced carbon nanotubes threaded with hollow Co 3 S 4 as the S host, which showed the competitive cycling stability of 718 mA g −1 after 300 cycles at 0.2 C ( Figure a–c). C@TiN dual‐shell nanospheres as electrodes exhibited an average discharge capacity of 1149, 934, 761, 591, and 373 mAh g −1 at 0.2, 0.5, 1.0, 2.0, and 5.0 C, respectively, as shown in Figure d–f.…”
Section: Energy Applicationsmentioning
confidence: 99%
“…f) the charge/discharge profiles of C@TiN‐S. a–c) Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Energy Applicationsmentioning
confidence: 99%
“…And at an areal sulfur loading of 2.3 mg cm −2 , the high-performance NiS sulfur cathode can provide a retaining capacity of 695 mAh g −1 after 300 cycles at a current density of 837.5 mA g −1 with a capacity retention of 96%. Chen et al [202] also reported that a spineltype metal sulfide, the Co 3 S 4 nanoboxes, can deliver a high conductivity of 3.3 × 10 3 S cm −1 and can be used as the highperformance sulfur host in Li-S batteries as well. In this study, Co 3 S 4 nanoboxes threaded by CNTs can be synthesized via a self-template approach in which the architecture is based on CNT 3D conductive pathways, and Co 3 S 4 can serve as chemical adsorption sites for lithium polysulfides.…”
Section: Inorganic Carbon-based Compositesmentioning
confidence: 99%